Screening and evaluating of long noncoding RNAs in the puberty of goats. (December 2017) - Gao, Xiaoxiao; Ye, Jing; Yang, Chen; Zhang, Kaifa; Li, Xiumei; Luo, Lei; Ding, Jianping; Li, Yunsheng; Cao, Hongguo; Ling, Yinghui; Zhang, Xiaorong; Liu, Ya; et al.
Abstract Background Long noncoding RNAs (lncRNAs) are involved in regulating animal development, however, their function in the onset of puberty in goats remain largely unexplored. To identify the genes controlling the regulation of puberty in goats, we measured lncRNA and mRNA expression levels from the hypothalamus. Results We applied RNA sequencing analysis to examine the hypothalamus of pubertal (case;n  = 3) and prepubertal (control;n  = 3) goats. Our results showed 2943 predicted lncRNAs, including 2012 differentially expressed lncRNAs, which corresponded to 5412 target genes. We also investigated the role of lncRNAs that actcis andtrans to the target genes and found a number of lncRNAs involved in the regulation of puberty and reproduction, as well as several pathways related to these processes. For example, oxytocin signaling pathway, sterol biosynthetic process, and pheromone receptor activity signaling pathway were enriched as Kyoto Encyclopedia of Genes and Genomes (KEGG) or gene ontology (GO) analyses showed. Conclusion Our results clearly demonstrate that lncRNAs play an important role in regulating puberty in goats. However, further research is needed to explore the functions of lncRNAs and their predicted targets to provide a detailed expression profile of lncRNAs on goat puberty.